Impact of last lenalidomide dose, duration, and IMiD-free interval in patients with myeloma treated with pomalidomide/dexamethasone - Efstathios Kastritis; Maria Roussou; Maria Gavriatopoulou; Nikolaos Kanellias; Magdalini Migkou; Evangelos Eleutherakis-Papaiakovou; Dimitrios C. Ziogas; Despina Fotiou; Ioannis Ntanasis-Stathopoulos; Ioanna Dialoupi; Stavroula Giannouli; Panagiotis Tsirigotis; et al. (Blood Advances, 2019)
Abstract: To gain insights into the characteristics of clinical resistance to lenalidomide, we evaluated the outcomes of 147 consecutive patients with multiple myeloma (MM) homogeneously treated with immunomodulatory imide drugs (IMiDs) pomalidomide and dexamethasone (Pd) for relapsed and/or refractory MM (median, 3 prior lines of treatment). We focused our analysis on the effect of the lenalidomide dose at which resistance was developed, the duration of lenalidomide exposure, and lenalidomide-free interval. On intent to treat, 33% of patients achieved ≥partial remission (PR) with Pd. When Pd was given immediately after lenalidomide, ≥PR was 32% (vs 37% after bortezomib). The response rates were similar for patients that received 5 to 15 mg vs 25 mg of lenalidomide (38.5% vs 30.5%, P = .329). Response rates were higher for patients that had received at least 12 months of lenalidomide (44% vs 27%) and for those with ≥18 months from last lenalidomide dose to pomalidomide dose (65% vs 23%). Median progression-free survival (PFS) and overall survival (OS) were 5 and 12.1 months, respectively, which was similar for patients who received lenalidomide, bortezomib or other regimens just before Pd and similar for patients who were receiving different doses of lenalidomide. IMiD-free interval ≥18 months was associated with longer PFS (10.3 vs 3.9 months, P = .003) and OS (27.1 vs 9.3, P = .008) as well as duration of last lenalidomide therapy ≥12 months (PFS: 7.8 vs 3.2, P = .023; OS: 16.5 vs 7.9, P = .005) even after adjustment for the number of prior therapies, duration of disease, and last lenalidomide dose.